Two And Three Dimensional Two And Three Dimensional Arts Learning Media Through Video Tutorials - Fistaningrumï¸, Riski Maulida; Setiawan, Deni (Universitas Negeri Semarang, 2021)
This study at develop designs, determine the viability and effectiveness of video tutorial media as a medium for learning two- and three-dimensional arts for the second grade students at Bebengan 3 Elementary School. The type of this research was Research and Development with a development model by Sugiyono. The data collection techniques used tests, interviews, documentation, and questionnaires. Based on the evaluation by the content expert validator, it was declared very viable with a percentage of 92.5%, and the media expert's assessment with a percentage of 94.23% with very viable criteria. The results of the small group t test used paired sample t-test obtained tcount of -8, 437 and t table with️= 5% which is equal to 2.571, so that Ho was rejected and B 0. The N-Gain test obtained a score of 0.67 with medium criteria. The conclusion from this research is that the video tutorial media was very viable and effective to be used in arts and culture subject of two and three dimensional artstopic in the second grade at Bebengan 3 Elementary School.Keywords: Art and Culture, Learning Media, Video Tutorials